Strategic Approaches for Sustainable Success: Navigating Corporate Strategy in Dynamic Markets - Rachel John Robinson (Business, Management and Economics: Research Progress Vol. 6, 2024)
This chapter details the varied nature of corporate strategy for achieving sustainable success in dynamic markets, focusing on the critical role of Strategic Business Units (SBUs) in guiding product and market decisions. It highlights essential business qualities such as flexibility, swiftness, and risk-taking. The primary methodologies discussed include cost leadership, differentiation, and focus strategies, with emphasis on market dissemination and new product development in volatile industries like tourism. The chapter underscores the importance of organizational structure, human resources, controlling systems, corporate culture, and comprehensive strategy processes. Additionally, it emphasizes evaluating strategic feasibility, and suitability, along with stakeholder and competitor management. The chapter concludes by promoting adaptive strategic planning to ensure sustainability and survival amid competitive pressures.